Teaching, Learning, and Management: International Student in China During the COVID-19 Pandemic - Wen, Guangrui; Tian, Mei (Journal of International Students, 2022)
The COVID-19 pandemic presents unprecedented challenges to the management, teaching, and learning in Chinese international education. This special issue focuses on national policies on international student education, institutional risk-management strategies, quality assurance practices, online teaching pedagogy, international student engagement, and factors affecting their satisfaction. We hope that the discussions in this special issue will allow us to share the lessons that we have learned during this crisis, promote international cooperation to cope with common challenges, and support the sustainable development and transformation of international education in China and worldwide in the post-COVID era.